2014
DOI: 10.1021/ar500103g
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances toward a General Purpose Linear-Scaling Quantum Force Field

Abstract: ConspectusThere is need in the molecular simulation community to develop new quantum mechanical (QM) methods that can be routinely applied to the simulation of large molecular systems in complex, heterogeneous condensed phase environments. Although conventional methods, such as the hybrid quantum mechanical/molecular mechanical (QM/MM) method, are adequate for many problems, there remain other applications that demand a fully quantum mechanical approach. QM methods are generally required in applications that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 41 publications
0
55
0
Order By: Relevance
“…21,22,8284,84–92 In this section, we emphasize the differences between fragment algorithms through the discussion of four types of methods: The “Divide-and-Conquer” (DC) LSQM method.The Fragment Molecular Orbital (FMO) LSQM method.Force fields founded upon underlying QM calculations, such as the Effective Fragment Potential (EFP), the Sum of Interactions between Fragments Ab initio (SIBFA), and Gaussian Electrostatic Model (GEM) methods.The eXplicit Polarization (X-Pol) and modified Divide-and-Conquer (mDC) QMFF methods.…”
Section: Inter-fragment Coupling Schemesmentioning
confidence: 99%
See 3 more Smart Citations
“…21,22,8284,84–92 In this section, we emphasize the differences between fragment algorithms through the discussion of four types of methods: The “Divide-and-Conquer” (DC) LSQM method.The Fragment Molecular Orbital (FMO) LSQM method.Force fields founded upon underlying QM calculations, such as the Effective Fragment Potential (EFP), the Sum of Interactions between Fragments Ab initio (SIBFA), and Gaussian Electrostatic Model (GEM) methods.The eXplicit Polarization (X-Pol) and modified Divide-and-Conquer (mDC) QMFF methods.…”
Section: Inter-fragment Coupling Schemesmentioning
confidence: 99%
“…Consequently, it has been shown that water clusters lose their hydrogen bond angles, instead choosing to adopt TIP3P-like, 133 planar hydrogen bonding motifs. 21,59,61 To correct for this deficiency, the mDC method concocts a new, auxiliary atomic multipole representation of the fragment density that is solely used for the inter-fragment Coulomb interactions.…”
Section: Inter-fragment Coupling Schemesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most enzyme systems are far too large to treat with a fully quantum mechanical method, although recently advances in so-called linear-scaling quantum force fields may alter that paradigm (Giese, Chen, Huang, & York, 2014; Giese, Huang, Chen, & York, 2014). An attractive alternative that has been widely applied is to use so-called combined quantum mechanical/molecular mechanical (QM/MM) models (QMMM, enzyme reactions, electrostatic and steric stabilzation, 1976; QMMM, molecular dynamics, 1990).…”
Section: Modeling the Chemical Steps Of Catalysismentioning
confidence: 99%